2010
DOI: 10.4161/cbt.9.8.11264
|View full text |Cite
|
Sign up to set email alerts
|

Conatumumab, a fully human agonist antibody to death receptor 5, induces apoptosis via caspase activation in multiple tumor types

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) binds to death receptors 4 and 5 (DR4, DR5) to transduce apoptotic signals. Conatumumab (AMG 655) is an investigational, fully human monoclonal agonist antibody (IgG(1)) to human DR5, which induces apoptosis via caspase activation. In this study, we demonstrate that conatumumab binds to DR5, activating intracellular caspases in vitro in the presence of a cross-linker. We also show that conatumumab has activity in vivo and inhibits tumor growth in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 41 publications
5
110
0
Order By: Relevance
“…The continuing challenge in these methodologies, as opposed to conventional chemotherapeutics that target all rapidly dividing cells, is to be able to specifically discriminate between tumor cells and their healthy counterparts without loss in efficacy. For conventional DR5 agonistic antibodies, such as drozitumab and conatumumab, efficacy is strongly dependent on cross-linking that is mediated by FcgRs in in vivo mouse models (11,13,25). However, despite very convincing and potent in vitro and in vivo preclinical data, this mode of agonistic antibody action has severe drawbacks that may explain the limited clinical efficacy observed for first-generation DR agonists (5,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…The continuing challenge in these methodologies, as opposed to conventional chemotherapeutics that target all rapidly dividing cells, is to be able to specifically discriminate between tumor cells and their healthy counterparts without loss in efficacy. For conventional DR5 agonistic antibodies, such as drozitumab and conatumumab, efficacy is strongly dependent on cross-linking that is mediated by FcgRs in in vivo mouse models (11,13,25). However, despite very convincing and potent in vitro and in vivo preclinical data, this mode of agonistic antibody action has severe drawbacks that may explain the limited clinical efficacy observed for first-generation DR agonists (5,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical data showed that conatumumab rapidly increased serum levels of activated caspase-3 in xenograft models of CRC, with peak levels detected approximately 12 to 24 hours after treatment (28). We investigated whether levels of activated caspase-3 similarly increased in the tumors of patients with CRC or NSCLC after dosing with conatumumab (preliminary antitumor activity was observed in CRC and NSCLC earlier in the study).…”
Section: Tumor Caspase-3 Activitymentioning
confidence: 99%
“…Conatumumab is an investigational, fully human monoclonal agonistic antibody (IgG1) directed against human DR5, which is expressed in many tumor types (11,(24)(25)(26)(27). In preclinical studies, conatumumab increased caspase activation, decreased cell survival, and inhibited tumor growth in a number of in vitro and in vivo models of human cancer, both as monotherapy and in combination with chemotherapeutic agents (28).…”
mentioning
confidence: 99%
“…For TRAIL-R agonists efficient clustering via the respective receptors DR4 and/or DR5 is an essential prerequisite for apoptosis induction. However, for most of the agonistic DR4 and DR5 antibodies, robust apoptosis induction in vitro is achieved only upon additional crosslinking via the Fc-part of the antibodies, suggesting that monomeric antibodies are not capable of clustering the critical number of receptors in order to trigger apoptosis (7,11,22,23). Although cross-linking is important to achieve sufficient potency in vitro, agonistic antibodies show excellent antitumor activity in vivo on human tumor xenografts.…”
Section: Introductionmentioning
confidence: 99%